Drawing a Comparison between Former Assumption University of Thailand (AU) Students’ Preferences for English Pronunciation Models at University Level with Their Exposure to English Pronunciation Models after Graduation - Tassev, Valentin (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2024)
The main goal of this study was to examine the relationship between former Assumption University of Thailand (AU) students’ preferences for English pronunciation models at the university level with their daily exposure to English pronunciation models after graduation, such as at work, and when socializing. In particular, this study drew a comparison between students’ preferences for pronunciation models of native speakers (NSs) of English with the pronunciation models of non-native speakers (NNSs) of English. The study utilized a questionnaire, and the data was analyzed both quantitatively and qualitatively. The results indicate that in students’ eyes, the NS English pronunciation models were the desired models to be learned at the university level. However, when examining students’ daily interactions in communicating in English after graduation, the study established that students communicated with NNSs of English more than with NSs and, thus, had higher levels of exposure to NNS norms. According to the findings, students might be to some extent biased toward NS norms, and, on these grounds, their preferences could be somehow socially-constructed and influenced by policies and practices supporting the ideology of native speakerism. On a further level, this study suggests that Thai learners of English need to learn and be exposed to a large variety of English pronunciation models, especially in international and intercultural settings, such as Thailand, where English is used more by NNS communicating with one another than with NSs.